Effectiveness of digital psychological and psychoeducational interventions to prevent anxiety: Systematic review and meta-analysis of randomized controlled trials - García-Huércano, Cristina; Conejo-Cerón, Sonia; Martínez-Vispo, Carmela; Bellón-Saameño, Juan Ángel; Rodríguez-Morejón, Alberto; Tamayo-Morales, Olaya; Moreno-Peral, Patricia (Cambridge University Press, 2025)
The high incidence of new cases of anxiety disorders highlights the need for scalable preventive interventions, which can be achieved through information and communication technologies. To our knowledge, no meta-analysis has been conducted to evaluate purely digital preventive interventions for anxiety in all types of populations. The aim of this study was to assess the effectiveness of digital interventions for the prevention of anxiety disorders. Systematic searches were conducted in six electronic databases (PubMed, PsycINFO, EMBASE, Web of Science, OpenGrey, and CENTRAL) from inception to December 12, 2024. Inclusion criteria for the studies were as follows: (1) randomized controlled trials (RCTs), (2) psychological or psychoeducational digital interventions to prevent anxiety, and (3) all types of populations without anxiety at baseline of the study. A total of 15 studies (19 comparisons; 6093 participants) were included in the systematic review. One study was identified as an outlier and was therefore excluded from the meta-analysis. The pooled analysis showed a small effect in favor of preventive interventions among non-anxious and varied populations (standardized mean difference = 0.32, 95% confidence interval: 0.44 to 0.20; p < 0.001). Sensitivity analyses supported the robustness of this finding. We found no evidence of publication bias. Heterogeneity was high, however, a meta-regression that included one variable (country, the Netherlands) explained 100% of the variance. All RCTs, except two, had a high risk of bias, and the quality of the evidence, according to Grading of Recommendations Assessment, Development, and Evaluation, was very low. There is a need to develop and evaluate new digital preventive interventions with a rigorous methodology.
Keywords: Angustia; Salud mental; Prevención; anxiety; digital health; prevention; randomized controlled trials